Environmental impact assessment of rapeseed production using the LCA method: Part one: Life cycle inventory analysis - Kiš Ferenc; Vasin Jovica; Milovac Željko; Zeremski Tijana; Milić Stanko; Savić Jasna (Selekcija i Semenarstvo, 2024)
This is the first part of an environmental life cycle assessment (LCA) study of oilseed rape cultivated under conditions prevalent in the region of Vojvodina, Serbia. The paper presents the initial two phases of the LCA: goal and scope definition, as well as the life cycle inventory (LCI). The assessment exclusively focuses on the rapeseed oil production chain, which includes the transportation of oilseeds to regional silos as its final stage. The assessment of production inputs, including quantities of mineral fertilizers, pesticides, and diesel fuel needed to achieve an assumed yield of 3000 kg ha-1, relies on recommendations from relevant agricultural advisory institutions. Emissions of pollutants into the environment, considered as outputs, are calculated using methodologies that account for locally specific conditions and production practices. Collected or estimated input and output data are entered into the OpenLCA software, which, in conjunction with the ecoinvent 3.7 database, computes the results of the LCI analysis. The LCI result contains data on hundreds of different pollutants emitted into the environment during the processes that make up the oilseed rape production chain, as well as a detailed inventory of consumed or used natural resources. However, LCI results only provide data on the quantities of different exchanges with the environment, not their potential impacts. Thus, they are not suitable for concluding the overall impact of oilseed rape production on the environment. Consequently, the analysis requires supplementation through the third LCA phase: the life cycle impact assessment (LCIA). This phase provides further explanations and interpretations of the significance of inventory results from an environmental protection perspective.